Evaluation of the potential genotoxic activity in seawater of Asin Bay, Gulf of Gulluk, Mugla, Aegean coast of Turkey - Kocak, E.; Sakar, S.; Yetilmezsoy, K.; Bozyigit, M.; Dalgic, G. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2017)
This research examined the genotoxic activity in the seawater of Asin Bay (Gulf of Gulluk) located in Mugla, Turkey, Aegean coast of Turkey. Genotoxic activities of 66 raw samples, taken from 17 different stations in the spring and summer seasons of the year 2013, were determined by using in vitro mutagenicity assay SOS chromotest with Escherichia coli PQ37 strain bacteria activities. In the applied procedure, beta-galactosidase (beta-gal) activity, alkaline phosphatase (AP) activity, and different solvent controls were taken into account to generate reliable results in terms of the corrected induction factors (CIF) used as a quantitative measure of genotoxic activity level. The SOS chromotest procedure was simply and rapidly performed as an early assay to explore for whether a potential genotoxic activity was presence in the in the seawater of Asin Bay (Gulf of Gulluk) with no special measuring devices except a microplate reader. The implemented assay was successfully completed within only 24 h including the revival of the bacteria. The results showed that 11 samples (% 17 of total) were close to the threshold value of 1.5. The findings of this study clearly revealed that the seawater of Asin Bay (Gulf of Gulluk) had no potential genotoxic risks in terms of the organisms in marine ecosystem, since all of the calculated CIF values were determined to be below the threshold level. It was concluded that according to the SOS chromotest results, the levels of potential genotoxic agents were found to be under the limits for the offshore fishery.
Keywords: Asin Bay; genotoxicity; Gulf of Gulluk; offshore fishery; SOS chromotest; WASTE-WATER GENOTOXICITY; SOS-CHROMOTEST; SENTINEL ORGANISMS; FLUCTUATION TEST; SURFACE WATERS; POLLUTION; ASSAY; INDUCTION; MUSSELS; SEA; Environmental Sciences & Ecology